Multilevel Analysis on Determinants of Diarrhea in Demak, Central Java - Aulia Noorvita Ramadani; Setyo Sri Rahardjo; Bhisma Murti (Masters Program in Public Health, 2019)
Background: Diarrhea is an infectious disease with high mortality in Indonesia. Diarrhea often occurs where risk factor control is weak, such as in rural area. This study aimed to examine the determinants of diarrhea in Demak, Central Java.Subjects and Method: A case-control study was conducted in Demak, Central Java, in October to November 2018. A sample of 200 study subjects was selected by fixed disease sampling. The dependent variable was diarrhea. The independent variables were age, clean water supply, latrine availability, waste water management, waste management, hand wash behavior, family income, and education level. The data were collected by questionnaire and analyzed by a multilevel regression, run on Stata 13.Results: Diarrhea increased with poor clean water supply (b= 1.45; 95% CI= 0.23 to 2.67; p= 0.020), latrine unavailable (b= 1.86; 95% CI= 0.66 to 3.06; p= 0.002), poor waste management (b= 2.71; 95% CI= 1.52 to 3.90; p<0.001), poor garbage management (b= 1.34; 95% CI= 0.17 to 2.50; p= 0.024), irregular hand washing with soap (b= 1.34; 95% CI= 0.12 to 2.40; p= 0.030). Diarrhea decreased with high family income (b= -1.56; 95% CI= -2.78 to -0.34; p= 0.012) and high education (b= -1.75; 95% CI= -2.95 to -0.565; p= 0.004). Diarrhea was negatively associated with age but it was statistically non-significant (b= -0.33; 95% CI= -1.51 to 0.844; p= 0.578). Village had contextual effect on the incidence of diarrhea (ICC= 13.9%).Conclusion: Diarrhea increases with poor clean water supply, latrine unavailable, poor waste management, poor garbage management, irregular hand washing with soap. Diarrhea decreases with high family income and high education. Village has contextual effect on the incidence of diarrhea.Keywords: diarrhea, water supply, hand wash behavior, waste managementCorrespondence: